Transformation of State-owned Hospitals to Private-owned: Are Selected Hospitals More Technical Efficient? - Lacko, Roman, 1988-
DEA - anlaýza obaľovania dát - metóda merania technickej efektívnosti podniku (nemocnice). DEA CCR input model, DEA BCC input model, DEA bootstrap model.